Preliminary assessment of the quality of coco vinegar from local producers - Tinambunan, Yvonne C. (2002.)
The quality of coco vinegar from the local producers in Miagao was assessed.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Coco vinegar; Vinegar